GROSS ALPHA/BETA ACTIVITY DETERMINATIONIN DRINKING WATER PROFICIENCY TESTS - Cfarku, Florinda; Berdufi, Irma (LPPM Universitas Jambi, 2024)
Water intended for drinking purposes has to be analyzed first for gross alpha/beta activity according to national and international standards and recommendations. According to Albanian legislation, Article 6, the gross alpha/beta radioactivity concentration in water, should be below the level of 0.1 Bq/L and 1 Bq/L respectively for human consumption. Our laboratory participated in an interlaboratory comparison organized by IAEA Terrestrial Environmental Laboratory under suggestion of ALMERA members. Proficiency Test among environmental radioactivity monitoring laboratories for the determination of gross alpha/beta activity concentration in drinking water and contaminated surfaces (2018, 2020). Independent standard methods were used for the reference value determination. Each sample was pretreated on site with nitric acid until reaching a pH level below 2. By creating relatively non-polar surfaces, this procedure avoids a loss of radionuclide fractions due to absorption into the walls of the containers.The Gross alpha/beta activity measurements were done using gas-flow proportional counter (GPC) method. The total dissolved solids should not exceed a surface density of 5 mg/cm2 for gross alpha determination and 10 mg/cm2 for gross beta determination The performance of participating laboratories was evaluated with respect to the reference values using relative deviations. The results presented from our laboratory in both inter comparisons (IAEA-TEL-2018-03) and (IAEA-TEL-2020-03) were all acceptable. The laboratory for the measurement of gross alpha/beta radioactivity and our Institute as a part of Tirana University is in the process of accreditation, so far the participation in the inter comparisons exercise is very important.